Temperature Dependence of Lattice Thermal Conductivity for some I-III-VI2 Group Compound Semiconductors - Omer, Mustafa S.; Ahmad, Hameed M.; Mamand, Suran M. (Sulaimani Journal for Pure and Applied Sciences, 2004)
Callaway formula is used to invesfigate the lattice thermal conductivity for nine compounds from the ternary group I-III-VI2 semicanductors at the temperature range from 5 to 300K. The maximum conductivities are found to be inthe tenrperature range 5-15K.The effects of the Debye temperature on lattice thermal conductivity as weil as maximum conductivity are invesfigated in some details. Many imperical formula are found to relate these compounds with their lattice thermal conductivities. The effects of carrier impurities (N) on this type of conductivity for the compound CuInSe2 are investigated and the N^ dependence is fcrund.
Keywords: Lattice thermal conductivity; ternary compounds; semiconductor impurity effects